2000
DOI: 10.1021/la991200v
|View full text |Cite
|
Sign up to set email alerts
|

In Situ ATR−FTIR Analysis of Surfactant Adsorption onto Silicon from Buffered Hydrofluoric Acid Solutions

Abstract: Buffered hydrofluoric acid (BHF) solutions containing HF and NH4F are widely used in the manufacturing of silicon-based integrated circuits. The adsorption/desorption characteristics of a commercially available, high purity, polyglycidol type surfactant (OHS) onto/from silicon from buffered hydrofluoric acid (BHF) solutions was studied by in situ attenuated total reflection-Fourier transform infrared spectroscopy (ATR-FTIR). The challenge in these measurements was to resolve the C-H peaks, in the 2800-3000 cm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Pendant bubble tensiometry has also been used to measure non-ionic surfactant adsorption at an air-water interface, where the equilibria and kinetics were fit to Langmuir and Frumkin models. 48 Attenuated total reflection (ATR) Fourier transform infrared (FT-IR) measurements have also been employed to investigate surfactant adsorption kinetics on the surfaces of infrared-transparent substrates such as silicon 49 and germanium. 50 In the present study, in situ SERS is employed to measure the equilibria and kinetics of surfactant adsorption from aqueous solution to a hydrophobic surface prepared by the assembly of an alkylsilane monolayer on an immobilized gold colloid film.…”
Section: Introductionmentioning
confidence: 99%
“…Pendant bubble tensiometry has also been used to measure non-ionic surfactant adsorption at an air-water interface, where the equilibria and kinetics were fit to Langmuir and Frumkin models. 48 Attenuated total reflection (ATR) Fourier transform infrared (FT-IR) measurements have also been employed to investigate surfactant adsorption kinetics on the surfaces of infrared-transparent substrates such as silicon 49 and germanium. 50 In the present study, in situ SERS is employed to measure the equilibria and kinetics of surfactant adsorption from aqueous solution to a hydrophobic surface prepared by the assembly of an alkylsilane monolayer on an immobilized gold colloid film.…”
Section: Introductionmentioning
confidence: 99%
“…In the Fourier transform infrared (FT-IR) spectrum of AN (Figure e), the characteristic peaks at 3100–3300, 3032, and 2798 cm –1 are assigned to the NH 4 + cations of AN . Additionally, the characteristic peaks of the NO 3 – anions are observed at 1384 and 826 cm –1 .…”
Section: Resultsmentioning
confidence: 97%
“…52,53 In the Fourier transform infrared (FT-IR) spectrum of AN (Figure 3e), the characteristic peaks at 3100−3300, 3032, and 2798 cm −1 are assigned to the NH 4 + cations of AN. 54 Additionally, the characteristic peaks of the NO 3 − anions are observed at 1384 and 826 cm −1 . 55 In the FT-IR spectrum of the MO/SA@AN particles, however, new adsorption bands assigned to −CH 3 (2954 cm −1 ), −CH 2 (2915 and 2851 cm −1 ), and −C�C− (1626 cm −1 ) groups appear, 56 indicating that the MO/SA hybrid coating has been successfully deposited on the AN particles.…”
Section: ■ Experimental Sectionmentioning
confidence: 96%
“…Furthermore, studies have shown that protonated amine groups are strongly hydrated compared to unprotonated amine groups. 17,18 Previously, surfactant adsorption has been studied using a variety of methods, including high-performance liquid chromatography, 19,20 reflectometry, 21 UV spectrophotometry, 22 Fourier transform infrared (FTIR) spectrocopy, 23,24 and ellipsometry, 25 and while they have captured the equilibrium adsorption of a wide variety of surfactants and substrates, they have difficulty capturing adsorption dynamics. Methods such as in situ attenuated total reflection−FTIR, which is able to measure the kinetics of surfactant adsorption, are limited by the need for approximations of numerous fitting parameters during data analysis.…”
Section: ■ Introductionmentioning
confidence: 99%